2023
DOI: 10.1001/jamanetworkopen.2023.40313
|View full text |Cite
|
Sign up to set email alerts
|

Use of Urea for the Syndrome of Inappropriate Secretion of Antidiuretic Hormone

Ralph Wendt,
Andrew Z. Fenves,
Benjamin P. Geisler

Abstract: ImportanceHyponatremia and the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) are associated with significant mortality and morbidity. The effectiveness and safety of oral urea for SIADH are still debated.ObjectiveTo evaluate the efficacy and safety of urea for the treatment of SIADH.Evidence ReviewA systematic search of Medline and Embase was conducted for controlled and uncontrolled studies of urea for SIADH in adult patients. The primary outcome was serum sodium concentration after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
(151 reference statements)
0
3
0
Order By: Relevance
“…Since starting the patient on salt tablets four times a day did not produce satisfactory results, we started additionally started her on urea, an osmotic diuretic, to increase free water excretion. Current data on the use of urea for SIADH is limited, and a recent systematic review found no definite evidence for the use of urea as a treatment for SIADH [10]. However, our patient showed significant improvement with urea, providing anecdotal support for the consideration of oral urea in refractory SIADH.…”
Section: Discussionmentioning
confidence: 50%
“…Since starting the patient on salt tablets four times a day did not produce satisfactory results, we started additionally started her on urea, an osmotic diuretic, to increase free water excretion. Current data on the use of urea for SIADH is limited, and a recent systematic review found no definite evidence for the use of urea as a treatment for SIADH [10]. However, our patient showed significant improvement with urea, providing anecdotal support for the consideration of oral urea in refractory SIADH.…”
Section: Discussionmentioning
confidence: 50%
“…58 Desmopressin (dDAVP), an AVP analog, is stabler and has higher V2R selectivity than AVP. Exogenous dDAVP increases intracellular cAMP that promotes insertion of AQP2 and UT-A1 in the luminal membrane of principal cells by activating their phosphorylation, 59,60 which allows urea to diffuse into the inner medullary interstitium. 61,62 The decreased urea excretion and increased water reabsorption lead to hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…65 Also, oral urea is an effective treatment for SIADH but it could increase the burden on the liver and kidneys of patients, and is not suitable to use in patients with hepatic or renal failure. 60,65 Furthermore, loop diuretics promote urinary sodium in the absence of excessive blood volume, which may lead to further exacerbation of hyponatremia. More importantly, loop diuretics may cause acute kidney injury and electrolyte disorders such as hypokalemia.…”
Section: Discussionmentioning
confidence: 99%